2013
DOI: 10.1016/j.ijmyco.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis spoligotypes circulating in the Syrian population: A retrospective study

Abstract: A more inclusive study of the Syrian population is necessary to more accurately identify most of the prevailing families in the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
1
1
1
Order By: Relevance
“…The L4 genotype SIT53 by its ubiquitous characteristics, is definitively associated to more than one sublineage although it is also encompassed in L4.1.1 Ghana [16]. It showed a low prevalence (2%) in our study compared to earlier study from Lebanon (20%) [18], as well as to those reported from Egypt (33.8%) [35], Syria (31.3%) [33], Iraq (26.8%) [27], Iran (6.1%) [25], Algeria (25.3%) [36], Tunisia (10.5%) [37], and Italy (11.7%) [38]. This difference in prevalence between our results and others could be attributed to the low number of MTB isolates screened in this study.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The L4 genotype SIT53 by its ubiquitous characteristics, is definitively associated to more than one sublineage although it is also encompassed in L4.1.1 Ghana [16]. It showed a low prevalence (2%) in our study compared to earlier study from Lebanon (20%) [18], as well as to those reported from Egypt (33.8%) [35], Syria (31.3%) [33], Iraq (26.8%) [27], Iran (6.1%) [25], Algeria (25.3%) [36], Tunisia (10.5%) [37], and Italy (11.7%) [38]. This difference in prevalence between our results and others could be attributed to the low number of MTB isolates screened in this study.…”
Section: Discussioncontrasting
confidence: 54%
“…Generally, the CAS sublineages displayed more diverse spoligotypes, SIT25 and SIT26 being the most predominant ones, which might be linked to a yet undeciphered evolutionary dynamics of the L3 within the MTB isolates [31]. A high prevalence of CAS1-Delhi is indeed observed in Sudan (53.9%, SIT25 (35%) [32], Iraq (41.8%; SIT25 (14.2%), SIT26 (6%)) [27], Syria (10.4%; SIT25 and SIT26 (20%)) [33], and Pakistan (CAS 39%; SIT26 39%) [34].…”
Section: Discussionmentioning
confidence: 93%
“…Considering other countries outside Africa, we note that the proportion of 43.7% is like those of 40.6% and 43.6% found respectively in Chile and Syria [24,25]. Generally, this LAM family is the largest in Venezuela (65%), in the Mediterranean basin (for example, 34% in Algeria, 55% in Morocco, 30% in Spain) and in the Caribbean region (30%) [25,26].…”
Section: Discussionsupporting
confidence: 50%